The Impact of Covid-19 Pandemic towards the Resilience of Small Medium Enterprises (SMEs) in Malaysia. Issue 1 (1st September 2022) - Rashid, M F; Yusoff, N S; Kamarudin, K H
Abstract: The Covid-19 pandemic has impacted the entire world dramatically. The unprecedented Covid-19 pandemic has widely impacted on Malaysia's economy, especially towards the small-scale economic activities related to the small medium enterprises (SMEs). Therefore, this paper aims to determine the impact of the Covid-19 pandemic towards the resilience of SMEs in Johor, Malaysia. The research methodology employed a quantitative method through a survey method via questionnaire sampling of 60 owners involved in SMEs operators across the case study. The research finding indicated that the Covid-19 pandemic had a massive influence on the economy of the majority of SMEs operators, especially on their income generations which average losses in revenue of more than 50 percent during the Covid-19 pandemic compared to 2019. This resulted from the shutdown of their business activities to curb the spread of the Covid-19 pandemic. Other findings highlighted that the government's initiatives to address the economic impact of SMEs yet insufficient to sustain business activities and income generations for instance access to financing facilities, product marketing opportunities and others. Therefore, required immediate initiatives should be made by all the stakeholders to reduce the economic impacts among the SMEs.